Self‐Propelling Janus Particles for Hemostasis in Perforating and Irregular Wounds with Massive Hemorrhage. (19th August 2020) - Li, Qing; Hu, Enling; Yu, Kun; Xie, Ruiqi; Lu, Fei; Lu, Bitao; Bao, Rong; Zhao, Tianfu; Dai, Fangyin; Lan, Guangqian
Abstract: Achieving rapid and safe control of perforating and irregular hemorrhage, defined as bleeding wounds with irregular external and internal wound shape, located deep within complex and covert hemorrhage sites, is vital to decrease the risk of mortality during prehospital treatments and surgical procedures. However, current hemostatic materials do not control hemorrhage effectively as their ability to access the bleeding source and coagulate blood is limited. Here, a biphasic Janus self‐propelled hemostatic particle (MSS@CaCO3 ) is prepared via uniaxial growth of flower‐like calcium carbonate crystal (CaCO3 ) on negatively‐modified‐microporous starch (MSS). The as‐synthesized hemostatic particle (MSS@CaCO3 T) is loaded with thrombin and powered by the internal component CaCO3, with the collaborative use of protonated tranexamic acid. These particles are capable of traveling against the blood flow allowing them to access deep bleeding sites, inducing synergistic blood coagulation effects to effectively halt hemorrhaging. The self‐propelling Janus hemostatic particle is sufficiently available in the deep bleeding sites of liver and femoral artery hemorrhage models, wherein the hemorrhage is rapidly controlled in ≈50 s and ≈3 min, respectively. To the authors' knowledge, this is the first attempt of controlling hemorrhage using Janus hemostatic particles with a self‐propelling property. Abstract : To stop bleeding in irregular and deep wounds fast, smart particle drugs that could self‐drive against blood flow adversely are prepared. Due to the generation of a large number of CO2 gas bubbles by the particles, the particles themselves could be pushed into the narrow bleeding sites, which is the most outstanding advantage compared with similar bleeding‐control drugs.